(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the article considers the effect of surface roughness on the functioning of a specific mechanism. In case of proven dependence of the studied functional property of surface microgeometry, a process of optimization of the sought parameter is carried out, in which the methods of mathematical analysis and theoretic foundations of technology of appliance and mechanical engineering are used for the basis of the theoretical studies. As control parameters of the specified optimal microgeometry, deciding the given task, the so-called non-parametric criteria are used, namely graphical of certain surface-profile functions.